PBahan Ajar Digital Model Oe3c-Etnofisika Berbantuan Augmented Reality Untuk Meningkatkan Kemampuan Berpikir Kritis Dan Literasi Fisika Siswa - Saddia, Andi; Amir, Faizal; Hutapea, Bilferi (UNIVERSITAS MUHAMMADIYAH METRO, 2025)
This study aims to develop digital teaching materials using the OE3C-Ethnophysics model assisted by Augmented Reality (AR) to improve students' critical thinking skills and physics literacy in fluid material. The OE3C-Ethnophysics model assisted by Augmented Reality (AR) is an innovation in creating interactive learning by integrating digital technology with ethnophysics. This study uses the Research and Development (R&D) method with the 4D model, namely define, design, development and disseminate. The subjects of this study were students of SMA 3 Majene class XI IPA. Data analysis techniques used include qualitative and quantitative descriptive analysis. The results of this study indicate that the teaching materials are very valid and practical in improving critical thinking skills and physics science literacy in SMA Negeri 3 Majene. The OE3C-Ethnophysics model assisted by Augmented Reality (AR) strongly supports interactive physics learning based on digital technology and contributes to preserving local culture.